SOLAR ENERGY SYSTEMS IN THE RECONSTRUCTION OF HERITAGE HISTORICAL BUILDINGS OF THE NORTHERN TOWNS (FOR EXAMPLE SAINT-PETERSBURG) - Murgul, Vera (Journal of Applied Engineering Science, 2014)
The use of solar energy supply systems for the reconstruction of facilities, historical and cultural monuments, faces many difficulties. Particularly because of the need to preserve the outside shape of the building. It is necessary to find a method of integration of solar energy system supply, but not at the expense of the architectural heritage, and ensuring optimum production of solar energy. The method should not touch at all the façade of the architecture. The author proposes to allocate additional energy supply systems based on solar energy in the class of temporary structures, potentially separable from the capital base of the building. Hence, the creation of  the concept of Building-independent temporary photovoltaics constructions (BITPVC). This article is dedicated to the issues of architectural adaptation and harmonious integration of solar energy technologies in the historic environment of the northern towns (for example Saint-Petersburg).
Keywords: Restoration; Reconstruction; Energy efficiency; Heritage historical buildings; Photovoltaic systems; Solar power